2020
DOI: 10.4317/medoral.23207
|View full text |Cite
|
Sign up to set email alerts
|

Awareness on oral cancer among patients attending dental school clinics in Brazil

Abstract: Oral cancer knowledge in patients attending dental school clinics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Globally, it is estimated that 354,864 new cases of oral cancer occurred in 2018, with 177,384 deaths. In Brazil, oral cancer represents the 5th most frequent cancer among males, with an estimated 11,200 new cases in men and 3,500 in women each year of the 2018-2019 period (1,2). Early diagnosis represents one of the greatest challenges in oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, it is estimated that 354,864 new cases of oral cancer occurred in 2018, with 177,384 deaths. In Brazil, oral cancer represents the 5th most frequent cancer among males, with an estimated 11,200 new cases in men and 3,500 in women each year of the 2018-2019 period (1,2). Early diagnosis represents one of the greatest challenges in oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also reported by Babiker et al ,[ 12 ] Joseph et al ,[ 15 ] and Prado et al . [ 16 ] Different studies established the fact that unexplained/recurrent or chronic nonhealing mouth ulcer is a common presenting complaint in patients with oral malignancy. [ 16 17 ] Another important sign is a lump in the oral cavity, which has been recognized by 58.9% of the study participants as a sign of OC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Australia, Jordan, Kuwait, Sudan, and Brazil[ 12 13 14 15 16 ] have investigated of the dental students or dentist's awareness of oral cancer and premalignant lesions. These studies showed the necessary need to improve the knowledge on preventing and detecting oral cancer.…”
Section: Introductionmentioning
confidence: 99%